The Impact of Emotional Intelligences and Reward on Teacher’s Organizational Citizenship Behavior - Masduki Ahmad; Heni Rochimah (Universitas Negeri Makassar, 2021)
This analysis has been undertaken to demonstrate the life of the impact of emotional intelligence and reward on Organizational Citizenship Behavior in the Surakarta district. The methodology in this study uses a quantitative approach to multiple linear regression. The sample was carried out on 118 Teachers in Surakarta City. A closed questionnaire on the Google form based on the Likert scale was the testing instrument. T-test and F-test hypothesis testing. The conclusions show several conclusions, namely: 1) Emotional intelligence contributes positively and significantly to Organizational Citizenship Behavior in Surakarta City, meaning that emotional Organizational Citizenship Behavior can increase intelligence. 2) Incentives lead favorably and substantially to teachers in Surakarta City's Organizational Citizenship Behavior, where the incentive will improve teachers' Organizational Citizenship Behavior. 3) Emotional Intelligence and Compensation have an effect on Organizational Citizenship Behavior in Surakarta City with a determination coefficient value of 0.495 or 49.5%, namely, emotional intelligence and reward together contribute to Organizational Citizenship Behavior (Y) of 49.5%.